Efeito do treino de tarefas funcionais associado à estimulação elétrica na mobilidade de crianças com paralisia cerebral unilateral - Rejane Vale Goncalves (2017)
Background: Children with unilateral cerebral palsy (UCP) walk slower than normal children and have difficulty performing activities such as climbing and descending stairs, running and jumping. Their gait pattern is likely due to the reduced propulsive capability of the plantar flexor muscles during gait. Objective: The objective of this study was to investigate the effect of a task-oriented training program associated with functional electrical stimulation (FES) of the gastrocnemius muscle on the mobility of children with UCP. Design: The study employed a single case A-B design with follow-up; phase A (4 weeks), phase B: intervention (8 weeks) and follow-up phase (4 weeks). Methods: Kinematic and kinetic gait data of four children with UCP (3 girls and 1 boy; mean age: 5.8 years) were systematically measured, throughout the study, totaling 24 evaluations per subject (8 evaluations in each phase). The variables measured were gait speed, step length, impulsive torque of the lower limb during gait, peak of power generation of the ankle and hip during the terminal phase of gait and vertical stiffness of the lower limb, bilaterally. Gross motor function was evaluated with the Gross Motor Function Measure (GMFM) tested at four moments of the study. Intervention consisted of a task-oriented training program associated with FES on gastrocnemius muscle during impulsion of affected lower limb, for eight weeks, 50 minutes a day, three times per week. Functional activities included moving from sitting to standing, standing calf raises, walking up and down stairs and walking over ground. The two-standard-deviationband method was used to compare the gait outcome measures and the Gross Motor Ability Estimator software (GMAE) to compare the gross motor function measures. Results: Three children showed improvements on walking speed and step length. All children showed improvements on impulsive torque during intervention, which were maintained during follow-up. Three children had increased peak of power generation at the ankle and the change in vertical stiffness differed among children. All children showed improvement of gross motor function at the end of the study. Conclusion: Functional tasks training associated with activation of the gastrocnemius muscle during terminal stance phase of gait seems to have provided a more efficient propulsion mechanism for the affected lower limb, resulting in a longer step length on that side and increased walking speed. The intervention provided the children with a locomotion pattern different than the one they were used to, since they experienced walking with an additional resource provided by FES. This has impacted the ability to perform activities such as climbing and descending stairs, running and jumping. The results of this study support the recommendation to include the strengthening of the gastrocnemius muscle during functional tasks in the treatment plan for children with UCP.